Preparation process of aluminum foil for lithium battery positive electrode current collector with high corrosion resistance

CN117721469BActive Publication Date: 2026-11-03JIANGSU DINGSHENG NEW MATERIAL JOINT STOCK CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311750913.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-19
Publication Date
2026-11-03
Estimated Expiration
2043-12-19

AI Technical Summary

Technical Problem

传统锂电池正极集流体用铝箔在高温、高湿及强酸强碱环境下耐腐蚀性能较弱,影响电池性能和稳定性。

Method used

By employing alloy raw material proportions and refined preparation processes, including heat treatment, primary surface treatment (immersion in boric acid and boron nitride solution) and secondary surface treatment (etching with hydrofluoric acid and nitric acid combined with immersion in alumina and sodium silicate solution), the corrosion resistance of aluminum foil is significantly improved.

Benefits of technology

It significantly improves the corrosion resistance of aluminum foil, extends its service life, enhances the charge and discharge efficiency and cycle stability of the battery, and improves the overall performance of the battery.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application discloses a preparation process of an aluminum foil with high corrosion resistance for a lithium battery positive electrode current collector, and comprises the following steps: alloy raw materials are added into a smelting furnace according to a proportioning ratio for smelting, the melt is treated by stirring and by introducing a slagging agent and a refining agent to obtain a melt, the melt is subjected to a degassing device to eliminate hydrogen existing in the melt, and a cast-rolling coil is obtained; the cast-rolling coil is transferred to an annealing furnace for heat treatment processing; after the heat treatment processing, primary surface treatment is carried out, the treated aluminum coil semi-finished product is cold-rolled into a finished product aluminum coil; the finished product aluminum coil is subjected to straightening and cleaning; slitting and finished product annealing are carried out, and finally, secondary surface treatment is carried out on the surface of the aluminum foil. The preparation process changes the properties of the surface of the aluminum foil through specific chemical and physical treatment, so that the corrosion resistance of the aluminum foil and the charge-discharge efficiency of the battery are improved, the cycle stability of the battery is enhanced, and the energy density of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of aluminum foil preparation, and more specifically to a preparation process of aluminum foil for lithium battery positive electrode current collector with high corrosion resistance. Background Technology

[0002] Lithium-ion batteries are widely used in electric vehicles, portable electronic devices, and other fields due to their high energy density, long lifespan, and excellent charge-discharge performance. The positive electrode current collector is one of the key components of a lithium-ion battery, and aluminum foil is typically used as the current collector material. However, the aluminum foil used for traditional lithium battery positive electrode current collectors may be corroded during the manufacturing process, leading to a decrease in battery performance.

[0003] In modern industrial production, aluminum foil is widely used in electronic equipment and battery manufacturing due to its excellent electrical conductivity, chemical stability, and processing properties. However, aluminum foil has relatively weak corrosion resistance in high-temperature, high-humidity, and strong acid / alkali environments, which to some extent limits its use in high-end applications such as lithium batteries.

[0004] Especially in lithium battery manufacturing, the migration of lithium ions during charging and discharging can chemically react with the aluminum foil inside the battery, leading to corrosion of the aluminum foil surface and consequently affecting the battery's charging and discharging efficiency and cycle stability. Therefore, improving the corrosion resistance of aluminum foil and optimizing the battery's charging and discharging efficiency and cycle stability are urgent technical problems to be solved in the current aluminum foil and lithium battery manufacturing fields. Summary of the Invention

[0005] To address the shortcomings of existing technologies, a process for preparing aluminum foil for lithium battery positive electrode current collectors with high corrosion resistance is provided. The specific scheme is as follows:

[0006] A process for preparing aluminum foil for lithium battery positive electrode current collectors with high corrosion resistance includes the following steps: alloy raw materials are added to a melting furnace according to a certain ratio for melting; the melt is treated by stirring and introducing slag remover and refining agent to obtain a melt; the melt is then introduced into a degassing device to remove hydrogen present in the melt, resulting in a cast-rolled coil; the cast-rolled coil is transferred to an annealing furnace for heat treatment; after heat treatment, a surface treatment is performed; the treated aluminum coil semi-finished product is cold-rolled into a finished aluminum coil; the finished aluminum coil is straightened and cleaned; it is then slit and annealed; finally, a second surface treatment is performed on the aluminum foil surface.

[0007] Furthermore, the first surface treatment includes the following steps: immersing the heat-treated aluminum coil semi-finished product in a solution composed of boric acid and boron nitride, with a solution concentration of 5-10%, for 30-60 minutes, and the temperature controlled at 60-80℃; then removing it, rinsing it with clean water, and then drying it.

[0008] Furthermore, the secondary surface treatment includes the following steps: First, a solution composed of hydrofluoric acid and nitric acid is used, with a concentration of 10-15%, an etching time of 5-10 minutes, and a temperature controlled at 20-30°C; then, the etched aluminum coil is physically ground for 10-15 minutes; the ground aluminum coil is then immersed in a solution composed of alumina and sodium silicate, with a concentration of 3-5%, an immersion time of 15-30 minutes, and a temperature controlled at 50-70°C; finally, the ground and immersed aluminum coil is removed, rinsed with clean water, and then dried.

[0009] Furthermore, the alloy raw material composition is as follows: 0.2-0.4% Si, 1.2-1.3% Fe, 0.2-0.3% Cu, 0.05-0.1% Zr, 0.05-0.1% Ti, 0.02-0.05% B, with the remainder being Al and unavoidable impurities.

[0010] Furthermore, the aluminum coil is rolled to a thickness of 0.2 mm in 6 passes. For the first 3 passes, the work roll roughness is Ra 0.75 μm and the rolling speed is 250–400 m / min; for the next 2 passes, the work roll roughness is Ra 0.65 μm and the rolling speed is 400–500 m / min; for the last pass, the work roll roughness is Ra 0.55 μm and the rolling speed is 550–600 m / min, thus obtaining the cold-rolled finished aluminum coil.

[0011] Furthermore, the cast-rolled coil undergoes billet annealing. The furnace gas temperature is raised to 280℃ at a heating rate of 20℃ / h to 30℃ / h and held for 6 hours. Then, the furnace gas temperature is raised to 380℃ at a heating rate of 50℃ / h and held for 4 hours. Finally, the furnace gas temperature is raised to 440 to 460℃ at a heating rate of 20℃ / h and held for 3 to 5 hours before being cooled and removed from the furnace, followed by rapid air cooling.

[0012] Furthermore, the characteristic feature is that the melting temperature is 730–740°C.

[0013] Furthermore, during the casting and rolling process, the temperature drop rate of the cooling zone is controlled at 140–150 °C / s.

[0014] Beneficial effects:

[0015] This invention provides a process for preparing aluminum foil for lithium battery positive electrode current collectors with high corrosion resistance, which has the following advantages:

[0016] (1) Significantly Improved Corrosion Resistance: By performing primary and secondary surface treatment processes sequentially during the preparation of aluminum foil, the corrosion resistance of the aluminum foil can be effectively improved. This treatment method can significantly reduce the loss of aluminum foil in highly corrosive environments, further improving the stability and service life of the aluminum foil. Especially during the long-term use of lithium batteries, it can effectively prevent the corrosion of aluminum foil and improve battery safety.

[0017] (2) Improve battery performance: Surface treatment can effectively change the physical and chemical properties of the aluminum foil surface, thereby improving the electrochemical performance of the battery, including optimizing the battery's charge and discharge efficiency, enhancing the battery's cycle stability, and increasing the battery's energy density, thereby improving the overall performance of the battery. Detailed Implementation

[0018] To enhance understanding of the present invention, the present invention will be further described in detail below with reference to embodiments. These embodiments are only used to explain the present invention and do not constitute a limitation on the scope of protection of the present invention.

[0019] Example 1:

[0020] A process for preparing aluminum foil for lithium battery positive electrode current collectors with high corrosion resistance includes the following steps:

[0021] First, the alloy raw materials are added to the melting furnace in the following proportions for melting: 0.3% Si, 1.25% Fe, 0.25% Cu, 0.08% Zr, 0.08% Ti, 0.03% B, with the remainder being Al and unavoidable impurities. The melting temperature is controlled at 730℃. After stirring and treating the melt with slag remover and refining agent, the melt is then introduced into a degassing device to remove any hydrogen present, yielding the cast-rolled coil. During the casting and rolling process, the temperature drop rate in the casting and rolling zone is controlled at 145℃ / s.

[0022] The cast-rolled coil is then transferred to an annealing furnace for billet annealing. The furnace gas temperature is raised to 280℃ at a heating rate of 25℃ / h and held for 6 hours. Then, the furnace gas temperature is raised to 380℃ at a heating rate of 50℃ / h and held for 4 hours. Finally, the furnace gas temperature is raised to 450℃ at a heating rate of 20℃ / h and held for 4 hours before being cooled and removed from the furnace and rapidly air-cooled.

[0023] After heat treatment, a surface treatment is performed: the heat-treated aluminum coil semi-finished product is immersed in a solution composed of boric acid and boron nitride with a concentration of 7% for 45 minutes at a temperature of 70°C; then it is taken out, rinsed with clean water, and then dried.

[0024] The processed aluminum coil semi-finished product is cold-rolled into finished aluminum coil. The aluminum coil is rolled to a thickness of 0.2 mm in 6 passes. For the first 3 passes, the work roll roughness is Ra 0.75 μm and the rolling speed is 350 m / min; for the next 2 passes, the work roll roughness is Ra 0.65 μm and the rolling speed is 450 m / min; for the last pass, the work roll roughness is Ra 0.55 μm and the rolling speed is 575 m / min; thus, the cold-rolled finished aluminum coil is obtained.

[0025] The finished aluminum coils are straightened, cleaned, slit, and annealed. Finally, the aluminum foil surface undergoes a second surface treatment: First, a solution composed of hydrofluoric acid and nitric acid with a concentration of 12% is used for etching for 7 minutes at a temperature of 25°C. Then, the etched aluminum coils are physically ground for 12 minutes. The ground aluminum coils are then immersed in a solution composed of alumina and sodium silicate with a concentration of 4% for 22 minutes at a temperature of 60°C. Finally, the ground and soaked aluminum coils are removed, rinsed with water, and then dried.

[0026] Example 2:

[0027] A process for preparing aluminum foil for lithium battery positive electrode current collectors with high corrosion resistance includes the following steps:

[0028] First, the alloy raw materials are added to the melting furnace in the following proportions for melting: 0.35% Si, 1.28% Fe, 0.28% Cu, 0.09% Zr, 0.09% Ti, 0.04% B, with the remainder being Al and unavoidable impurities. The melting temperature is controlled at 735℃. After stirring and treating the melt with slag remover and refining agent, the melt is then introduced into a degassing device to remove any hydrogen present, yielding the cast-rolled coil. During the casting and rolling process, the temperature drop rate in the casting and rolling zone is controlled at 140℃ / s.

[0029] The cast-rolled coil is then transferred to an annealing furnace for billet annealing. The furnace gas temperature is raised to 285°C at a heating rate of 30°C / h and held for 6 hours. Then, the furnace gas temperature is raised to 385°C at a heating rate of 45°C / h and held for 4 hours. Finally, the furnace gas temperature is raised to 455°C at a heating rate of 25°C / h and held for 4 hours before being cooled and removed from the furnace and rapidly air-cooled.

[0030] After heat treatment, a surface treatment is performed: the heat-treated aluminum coil semi-finished product is immersed in a solution composed of boric acid and boron nitride with a concentration of 8% for 50 minutes at a temperature of 75°C; then it is taken out, rinsed with clean water, and then dried.

[0031] The processed aluminum coil semi-finished product is cold-rolled into finished aluminum coil. The aluminum coil is rolled to a thickness of 0.2 mm in 6 passes. For the first 3 passes, the work roll roughness is Ra 0.75 μm and the rolling speed is 375 m / min; for the next 2 passes, the work roll roughness is Ra 0.65 μm and the rolling speed is 475 m / min; for the last pass, the work roll roughness is Ra 0.55 μm and the rolling speed is 585 m / min; thus, the cold-rolled finished aluminum coil is obtained.

[0032] The finished aluminum coils are straightened, cleaned, slit, and annealed. Finally, the aluminum foil surface undergoes a second surface treatment: First, a solution composed of hydrofluoric acid and nitric acid with a concentration of 13% is used for etching for 8 minutes at a temperature of 28°C. Then, the etched aluminum coils are physically ground for 13 minutes. The ground aluminum coils are then immersed in a solution composed of alumina and sodium silicate with a concentration of 5% for 25 minutes at a temperature of 65°C. Finally, the ground and soaked aluminum coils are removed, rinsed with water, and then dried.

[0033] Example 3:

[0034] A process for preparing aluminum foil for lithium battery positive electrode current collectors with high corrosion resistance includes the following steps:

[0035] First, the alloy raw materials are added to the melting furnace in the following proportions for melting: 0.25% Si, 1.20% Fe, 0.22% Cu, 0.07% Zr, 0.07% Ti, 0.02% B, with the remainder being Al and unavoidable impurities. The melting temperature is controlled at 740℃. After stirring and treating the melt with slag remover and refining agent, the melt is then introduced into a degassing device to remove any hydrogen present, yielding the cast-rolled coil. During the casting and rolling process, the temperature drop rate in the casting and rolling zone is controlled at 150℃ / s.

[0036] The cast-rolled coil is then transferred to an annealing furnace for billet annealing. The furnace gas temperature is raised to 275°C at a heating rate of 20°C / h and held for 6 hours. Then, the furnace gas temperature is raised to 375°C at a heating rate of 55°C / h and held for 4 hours. Finally, the furnace gas temperature is raised to 445°C at a heating rate of 15°C / h and held for 4 hours before being cooled and removed from the furnace and rapidly air-cooled.

[0037] After heat treatment, a surface treatment is performed: the heat-treated aluminum coil semi-finished product is immersed in a solution composed of boric acid and boron nitride with a concentration of 6% for 40 minutes at a temperature of 65°C; then it is taken out, rinsed with clean water, and then dried.

[0038] The processed aluminum coil semi-finished product is cold-rolled into finished aluminum coil. The aluminum coil is rolled to a thickness of 0.2 mm in 6 passes. For the first 3 passes, the work roll roughness is Ra 0.75 μm and the rolling speed is 325 m / min; for the next 2 passes, the work roll roughness is Ra 0.65 μm and the rolling speed is 425 m / min; for the last pass, the work roll roughness is Ra 0.55 μm and the rolling speed is 565 m / min; thus, the cold-rolled finished aluminum coil is obtained.

[0039] The finished aluminum coils are straightened, cleaned, slit, and annealed. Finally, the aluminum foil surface undergoes a second surface treatment: First, a solution composed of hydrofluoric acid and nitric acid with a concentration of 11% is used for etching for 6 minutes at a temperature of 22°C. Then, the etched aluminum coils are physically ground for 11 minutes. The ground aluminum coils are then immersed in a solution composed of alumina and sodium silicate with a concentration of 3% for 20 minutes at a temperature of 55°C. Finally, the ground and soaked aluminum coils are removed, rinsed with water, and then dried.

[0040] Comparative example:

[0041] The preparation process is similar to that of Example 1, except that the aluminum foil is not surface treated during the production process.

[0042] The corrosion resistance of the aluminum foils prepared in Examples 1-3 and the comparative example was tested, and the test results are as follows:

[0043] In Example 1, after a 48-hour corrosion test, the aluminum foil prepared in Example 1 showed extremely low corrosion, with only a few tiny corrosion spots appearing, indicating that it has excellent corrosion resistance.

[0044] In Example 2, under the same corrosive environment, the aluminum foil prepared in Example 2 showed a slightly higher degree of corrosion than that in Example 1 after a 48-hour corrosion test, but it still remained at a low level, demonstrating that it has good corrosion resistance.

[0045] The aluminum foil prepared in Example 3 showed a corrosion degree between that of Example 1 and Example 2 after a 48-hour corrosion test, indicating good corrosion resistance.

[0046] In the same corrosive environment, the aluminum foil prepared in the comparative example showed a significantly higher degree of corrosion than that of Examples 1-3 after 48 hours of corrosion testing. A large number of corrosion spots were distributed on the surface of the aluminum foil, indicating that the aluminum foil without surface treatment had poor corrosion resistance.

[0047] Therefore, the preparation process of the aluminum foil for lithium battery positive electrode current collector with high corrosion resistance described in Examples 1-3, through reasonable alloy raw material ratio and fine preparation process, especially the surface treatment step, can effectively improve the corrosion resistance of aluminum foil, which is beneficial to improving the stability and service life of lithium battery.

[0048] As a further improvement, the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A process for preparing aluminum foil for lithium battery positive electrode current collectors with high corrosion resistance, characterized in that, Includes the following steps: Alloy raw materials are added to a melting furnace according to a certain ratio for melting. The melt is stirred and treated with slag remover and refining agent to obtain a melt. The melt is then put into a degassing device to remove hydrogen present in the melt, resulting in a cast-rolled coil. The cast-rolled coil is then transferred to an annealing furnace for heat treatment. After heat treatment, a surface treatment is performed. The treated aluminum coil semi-finished product is then cold-rolled into a finished aluminum coil. The finished aluminum coil is then straightened and cleaned. It is then slit and annealed. Finally, a second surface treatment is performed on the aluminum foil surface. The surface treatment includes the following steps: immersing the heat-treated aluminum coil semi-finished product in a solution composed of boric acid and boron nitride, with a solution concentration of 5-10%, for 30-60 minutes, and the temperature controlled at 60-80℃; then removing it, rinsing it with clean water, and then drying it. The secondary surface treatment includes the following steps: First, a solution composed of hydrofluoric acid and nitric acid with a concentration of 10-15% is used for etching for 5-10 minutes at a temperature of 20-30°C. Then, the etched aluminum coil is physically ground for 10-15 minutes. The ground aluminum coil is then immersed in a solution composed of alumina and sodium silicate with a concentration of 3-5% for 15-30 minutes at a temperature of 50-70°C. Finally, the ground and soaked aluminum coil is removed, rinsed with clean water, and then dried.

2. The preparation process of aluminum foil for lithium battery positive electrode current collector with high corrosion resistance according to claim 1, characterized in that, The alloy raw material composition is as follows: 0.2~0.4% Si, 1.2~1.3% Fe, 0.2~0.3% Cu, 0.05~0.1% Zr, 0.05~0.1% Ti, 0.02~0.05% B, with the remainder being Al and unavoidable impurities.

3. The preparation process of aluminum foil for lithium battery positive electrode current collector with high corrosion resistance according to claim 1, characterized in that, The aluminum coil is rolled to a thickness of 0.2 mm in 6 passes. For the first 3 passes, the work roll roughness is Ra 0.75 μm and the rolling speed is 250~400 m / min; for the next 2 passes, the work roll roughness is Ra 0.65 μm and the rolling speed is 400~500 m / min; for the last pass, the work roll roughness is Ra 0.55 μm and the rolling speed is 550~600 m / min; thus, the cold-rolled finished aluminum coil is obtained.

4. The preparation process of aluminum foil for lithium battery positive electrode current collector with high corrosion resistance according to claim 1, characterized in that, The cast-rolled coil is annealed by heating the furnace gas temperature at a rate of 20℃ / h~30℃ / h to 280℃ and holding it for 6 hours. Then, the furnace gas temperature is raised to 380℃ at a rate of 50℃ / h and held for 4 hours. Finally, the furnace gas temperature is raised to 440~460℃ at a rate of 20℃ / h and held for 3~5 hours before being cooled and removed from the furnace and rapidly air-cooled.

5. The preparation process of an aluminum foil with high corrosion resistance for lithium battery positive electrode current collector according to claim 1, characterized in that, The melting temperature is 730~740℃.

6. The preparation process of an aluminum foil with high corrosion resistance for lithium battery positive electrode current collector according to claim 1, characterized in that, During the casting and rolling process, the temperature drop rate in the casting and rolling zone is controlled at 140~150℃ / s.

Citation Information

Patent Citations

  • Aluminum foil and processing technology thereof

    CN117127231A